FAVA BEANS OF SUBSAMPLES SELECTION FOR RESISTANCE ANTHRACNOSE - Santos, A. R. B.; Simeão, M.; Barros, P. S.; Cavalcante, G. R. dos S.; Carvalho, E. M. S. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The aim of this experiment, using detached leaf, selecting resistant bean-bean subsamples or with some degree of resistance to anthracnose to contribute to crop yield of elevation. The leaves were inoculated 40 days after planting, where you can select uniform leaves with a suspension of Colletotrichum truncatum spores and severity was visually assessed by two reviewers at five and seven days after inoculation (DAI), using a scale notes ranging from 0 to 5. The design used in this experiment was completely randomized with four repetitions, each repetition consists of a fully expanded trifoliate leaf. The subsamples have evaluated variable anthracnose resistance level. The majority (84.21%) is highly susceptible, only a subsample (1.75%) is highly resistant (UFPI-503) and three samples (5.26%) moderately resistant (UFPI-237, UFPI-466 and UFPI -134) and is therefore promising in breeding program aimed at selecting materials more productive and resistant to disease.